INFLUENCE OF PRESTRESSING FORCE ON BOX GIRDER BRIDGE SUBJECTED TO SEISMIC LOAD (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Bridges are often considered to be engineering marvels. Whether we need to cross rivers or valleys, connect islands to mainland, carry cars people etc are obstacles that are achieved only by bridges. Pre stressed concrete is ideally suited for the construction of medium to long span bridges. The composition of pre stressed concrete is nothing but high strength concrete and high tensile steel which is aesthetically appealing and economical. The present study deals with the analysis of reinforced concrete and prestressed concrete bridges. Reinforced concrete and Post-tensioned bridges of spans 15m, 30m and 45m are considered. Analysis of these bridges is performed with SAP2000 software for various Earthquake zones. The bending moments due to load combinations, viz.,(Dead load+ live load), (Dead load+ Earthquake load in X-direction), (Dead load+ Earthquake load in Y-direction), (Dead load+ live load+ Earthquake load in X-direction) and (Dead load+ live load+ Earthquake load in Y-direction) by considering with and without application of prestressing are obtained and compared. Maximum deflections under these load combinations are obtained by considering with and without application of prestressing and compared.